Reactivation of cyclosarin-inhibited rat brain acetylcholinesterase by pyridinium--oximes - Kuca, Kamil; Patocka, Jirí (Journal of enzyme inhibition and medicinal chemistry, 2004)
Cyclohexyl methylphosphonofluoridate (cyclosarin, cyclosin, GF) is a highly toxic organophosphate, which is resistant to conventional oxime therapy. To gain insight into the reactivation kinetics, rat brain acetylcholinesterase (AChE) was inhibited in vitro by cyclosarin (pH 8.0, 25 degrees C) and reactivated with 22 different pyridiniumoximes. Three compounds were shown to be superior to the other oximes: 4-carbamoyl-4'-[(hydroxyimino)methyl]-1,1'-(oxydimethylene)dipyridin-1-ium dichloride (HS-6), 4'-carbamoyl-2-[(hydroxyimino)methyl]-1,1'-(oxydimethylene)dipyridin-1-ium dichloride (HI-6), and 4'-carbamoyl-2-[(hydroxyimino)-methyl]-1,1'-(but-2-ene-1,4-diyl)dipyridin-1-ium dichloride (BI-6).
Keywords: pyridinové sloučeniny; oximy; mozek; Pyridinium Compounds; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Oximes; organofosforové sloučeniny; krysa rodu Rattus; zvířata; cholinesterasové inhibitory; Kinetics; kinetika; Brain; Acetylcholinesterase; Organophosphorus Compounds; reaktivátory cholinesterasy; Cholinesterase Reactivators; Rats; Animals; acetylcholinesterasa; Cholinesterase Inhibitors